Can Postoperative Distal Adding-On be Predicted in Lenke Type 1B and 1C Curves with Intraoperative Radiographs?. Issue 6 (15th March 2022) - Fujii, Takeshi; Kawabata, Soya; Suzuki, Satoshi; Tsuji, Osahiko; Nori, Satoshi; Okada, Eijiro; Nagoshi, Narihito; Yagi, Mitsuru; Michikawa, Takehiro; Nakamura, Masaya; Matsumoto, Morio; Watanabe, Kota
Abstract : Selecting the last touching vertebra as the lowest instrumented vertebra (LIV) may prevent postoperative distal adding-on (DA) in Lenke Type 1B and C curves. LIV extension might be considered to avoid postoperative DA in patients whose first disc's angulation below the LIV is more than 3° in intraoperative radiographs. Abstract : Study Design: A retrospective study of consecutive collected data. Objective: To investigate risk factors for postoperative distal adding-on (DA) in Lenke Type 1B and 1C curves using intraoperative radiographs. Summary of Background Data: In adolescent idiopathic scoliosis (AIS), DA radiographic complication can negatively affect postoperative clinical results. However, few studies have focused on assessing risk factors for DA using intraoperative radiographs. Methods: We retrospectively evaluated 69 AIS patients with Lenke Type 1B or 1C curves who underwent posterior selective thoracic fusion. We divided patients into DA and non-DA groups based on radiograph data at 2-year follow-up using Wang et al (Spine 2011) definition of DA. We compared coronal radiographic parameters, including relative positions of end vertebra (EV), stable vertebra (SV), neutral vertebra (NV), and last touching vertebra (LTV) to lowest instrumented vertebra (LIV), and intraoperative radiographic parameters, between the two groups. Results: DA was present in 13 patients (18.8%) at 2-year follow-up. The mean LIV–EV, LIV–NV, LIV–SV, and LIV–LTV relative positions were significantly smaller in the DA group than in the non-DA group. Multivariate analysis showed that LIV–LTV was significantly associated with DA (DA: −0.2 ± 0.7, non-DA: 0.6 ± 0.7). Intraoperative radiographs showed that the mean angulation of the first disc below the LIV after final adjustment was significantly larger in the DA group (2.3° ± 1.1°) than in the non-DA group (0.9° ± 0.7°). Patients whose angulation of the first disc below the LIV was more than 3° were significantly associated with DA. Conclusion: The LIV selected at more cranial to the LTV may be a risk factor for postoperative DA in Lenke Type 1B and 1C curves. Moreover, it was suggested that LIV extension might be considered when the first disc's angulation below the LIV is >3° in intraoperative radiographs. Level of Evidence: 3